2023
DOI: 10.1002/smll.202308952
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electron Transfer in CdS Photocatalysts Decorated with Various Noble Metals

Zheng Meng,
Jianjun Zhang,
Chenchen Jiang
et al.

Abstract: To address charge recombination in photocatalysis, the prevalent approach involves the use of noble metal cocatalysts. However, the precise factors influencing this performance variability based on cocatalyst selection have remained elusive. In this study, CdS hollow spheres loaded with distinct noble metal nanoparticles (Pt, Au, and Ru) are investigated by femtosecond transient absorption (fs‐TA) spectroscopy. A more pronounced internal electric field leads to the creation of a larger Schottky barrier, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Fig. 4(d-f) show the Zn 2p, Cd 3d, and S 2p spectra, with signal peaks at 1022 and 1045 eV attributed to the Zn 2p 3/2 and 2p 1/2 orbitals, 32,33 405 and 411 eV to the Cd 3d 5/2 and 3d 3/2 orbitals, 34 and 161 and 162 eV to the S 2p 3/2 and 2p 1/2 orbitals, [35][36][37] respectively. By comparing the binding energy shifts, it is found that the introduction of ACu-MOF and Cu-MOF can effectively reduce the charge density on the surface of ZCS compared to ZCS alone.…”
Section: Synthesis and Structure Of The Catalystmentioning
confidence: 99%
“…Fig. 4(d-f) show the Zn 2p, Cd 3d, and S 2p spectra, with signal peaks at 1022 and 1045 eV attributed to the Zn 2p 3/2 and 2p 1/2 orbitals, 32,33 405 and 411 eV to the Cd 3d 5/2 and 3d 3/2 orbitals, 34 and 161 and 162 eV to the S 2p 3/2 and 2p 1/2 orbitals, [35][36][37] respectively. By comparing the binding energy shifts, it is found that the introduction of ACu-MOF and Cu-MOF can effectively reduce the charge density on the surface of ZCS compared to ZCS alone.…”
Section: Synthesis and Structure Of The Catalystmentioning
confidence: 99%